The Development of Halal-based Local Tourism in Gampong Nusa, Aceh - Alifa, Yumna (International Journal of Sustainable Competitiveness on Tourism, 2025)
In Acehnese society, religion and customs play a significant role in influencing the social structure and order. This is exemplified in one of the hadih madja, which reads, 'Adat bak Poe Teumeureuhom, Hukom bak Syiah Kuala, Qanun bak Putroe Phang, Reusam bak Lakseumana'. From a tourism perspective, Aceh's customary practices offer a framework that allows tourism activities to be conducted in a respectful manner that aligns with local traditions. Meanwhile, principles drawn from Islamic law (sharia) ensure that tourist services meet the needs of travelers in ways that align with the religious values and principles of those travelers. Qanun, as local regulations, provide guidelines for destination management, while reusam reflect customs that can be integrated into the tourism experience. This research employs a qualitative approach with case study analysis in Gampong Nusa to evaluate the efficacy of integrating these values in the development of authentic and sustainable tourism experiences. The findings demonstrate that incorporating these elements in the advancement of halal tourism not only enhances traveller satisfaction but also preserves and reinforces Acehnese culture. By establishing a precise target market and implementing an appropriate marketing strategy, Gampong Nusa has the potential to enhance its reputation as a halal tourist destination.